2020
DOI: 10.3389/fmats.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Study on Preparation and Properties of InN Films on Self-Supporting Diamond Substrates Under Different Nitrogen Flows

Abstract: Several InN film samples with superb properties were prepared on a self-supporting diamond substrate for different nitrogen flow rates using an electron cyclotron resonance plasma-enhanced metal-organic chemical vapor deposition (ECR-PEMOCVD) system. After the InN film samples were obtained, the samples were characterized via reflected high-energy electron diffraction (RHEED), X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscope (AFM), and electron probe micro-analysis (EPMA) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…An InN buffer layer is the innovation of this study. In previous work, we found that the proper technological parameters for InN film growth by ECR-PEMOCVD without introducing a buffer layer were a deposition temperature of 400 • C, a nitrogen flow rate of 80 sccm, and a TMIn flow rate of 0.6 sccm [26,27]. Under these conditions, the grain size of InN was 47 nm, the surface roughness was 3.7 nm, the background electron concentration was 9.2 × 10 19 cm −3 , and the carrier mobility was 48.5 cm 2 /V•s [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An InN buffer layer is the innovation of this study. In previous work, we found that the proper technological parameters for InN film growth by ECR-PEMOCVD without introducing a buffer layer were a deposition temperature of 400 • C, a nitrogen flow rate of 80 sccm, and a TMIn flow rate of 0.6 sccm [26,27]. Under these conditions, the grain size of InN was 47 nm, the surface roughness was 3.7 nm, the background electron concentration was 9.2 × 10 19 cm −3 , and the carrier mobility was 48.5 cm 2 /V•s [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we found that the proper technological parameters for InN film growth by ECR-PEMOCVD without introducing a buffer layer were a deposition temperature of 400 • C, a nitrogen flow rate of 80 sccm, and a TMIn flow rate of 0.6 sccm [26,27]. Under these conditions, the grain size of InN was 47 nm, the surface roughness was 3.7 nm, the background electron concentration was 9.2 × 10 19 cm −3 , and the carrier mobility was 48.5 cm 2 /V•s [26,27]. When an InN buffer layer was introduced with a deposition temperature of 100 • C, the grain size of InN film was 51 nm (4 nm larger) and the surface roughness was 2.4 nm (1.3 nm less).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is beneficial to produce nonstoichiometric MNs thin films with fewer impurities. Among various deposition methods, metal organic chemical vapor deposition is an effective method to synthesize 2D IIIANs, including AlN [185,187,193,429,430], GaN [232,233,243,245,249,251] and InN [305,308,431,432].…”
Section: Synthetic Routes Corresponding 2d Mnsmentioning
confidence: 99%